PEMBERDAYAAN MASYARAKAT DALAM MENINGKATKAN DAYA SAING DI DKI JAKARTA - Muh. Kadarisman (SWATANTRA, 2017)
This study aimed to analyze the empowerment of communities in improving competitiveness areas in Jakarta. This study uses a qualitative method. The results of the research, that the Jakarta public in general has demonstrated his ability by increasing capacity in the chores or their jobs. The ability of the people of Jakarta is essentially composed of two sets of factors, namely the intellectual ability and physical ability. Jakarta public has confidence to manage the program and take decisions independently, so as to explore the potential, initiative and creativity of the community. Furthermore, the growing competitiveness of the area indicated by the achievement of growth and the higher level of prosperity and sustainable, open to domestic and international competition, and the ability to further optimize natural resources and human resources and potentially more excavated. Knowledge and comparative advantages of the area, can be used by policy makers to encourage changes in the economic structure of Jakarta Capital City towards sectors that have competitive advantages.Keywords: community development, regional competitiveness